A Policy Examination of Covid-19 Impact on the Radiology Department Standard Operating Procedures (SOPs): The Malaysian Experience - Ahmad Luqmanulhakim Sunawari; Aisyah Rahimi; Aminatul Saadiah Abdul Jamil; Azira Khalil; Shahrina Ismail (USIM PRESS, 2024)
Malaysian Journal of Science, Health & Technology (MJoSHT) Volume 10 Issue 1 Page (88-98)